Hierarchical Bi2O2CO3 wrapped with modified graphene oxide for adsorption-enhanced photocatalytic inactivation of antibiotic resistant bacteria and resistance genes. (1st October 2020) - Li, Deyi; Yu, Pingfeng; Zhou, Xuefei; Kim, Jae-Hong; Zhang, Yalei; Alvarez, Pedro J.J.
Abstract: There is growing pressure for wastewater treatment plants to mitigate the discharge of antibiotic resistant bacteria (ARB) and extracellular resistance genes (eARGs), which requires technological innovation. Here, hierarchical Bi2 O2 CO3 microspheres were wrapped with nitrogen-doped, reduced graphene oxide (NRGO) for enhanced inactivation of multidrug-resistant E. coli NDM-1 and degradation of the plasmid-encoded ARG ( bla NDM-1 ) in secondary effluent. The NRGO shell enhanced reactive oxygen species (ROS) generation (OH and H2 O2 ) by about three-fold, which was ascribed to broadened light absorption region (red-shifted up to 459 nm) and decreased electron-transfer time (from 55.3 to 19.8 ns). Wrapping enhanced E. coli adsorption near photocatalytic sites to minimize ROS scavenging by background constituents, which contributed to the NRGO-wrapped microspheres significantly outperforming commercial TiO2 photocatalyst. ROS scavenger tests indicated that wrapping also changed the primary inactivation pathway, with photogenerated electron holes and surface-attached hydroxyl radicals becoming the predominant oxidizing species with wrapped microspheres, versus free ROS (e.g., OH, H2 O2 and O2 − ) for bare microspheres. Formation of resistance plasmid-composited microsphere complexes, primary due to the π-π stacking and hydrogen bonding between the shell and nucleotides, also minimized ROS scavenging and kept free plasmid concentrations below 10 2 copies/mL. As proof-of-concept, this work offers promising insight into the utilization of NRGO-wrapped microspheres for mitigating antibiotic resistance propagation in the environment. Graphical abstract: Image 1 Highlights: Nitrogen doping enhanced electron transfer and bacterial adsorption to RGO. This improved ROS generation and ARB inactivation near photocatalytic sites. Surface-bound oxidizing species were main contributors to ARB inactivation. eARGs released near catalytic sites were also efficiently degraded by NGWM.